Potencial interdisciplinarnih raziskav človeških skeletnih posmrtnih ostankov - Leskovar, Tamara (Arheološki vestnik, 2024)
The analysis of skeletal remains from archaeological contexts contributes significantly to the understanding of individuals and societies in the past. Using the quadruple grave 336–339 from the Late Antique cemetery of Bled Pristava as an example, we present the course and results of an integrated interdisciplinary research combining some of the most commonly conducted analyses in the study of skeletal tissues and placing their results in a larger archaeological and historical context. From the data collected, it can be concluded that the four deceased, a father with two daughters and a son, were placed in a common grave at the same time and intentionally, perhaps due to special circumstances at the time of death. Grave goods date the grave in the mid-6th century, radiocarbon dating to the 5th and first half of the 6th century. Stable isotope analysis reveals fluctuations in diet during different periods of life related to dietary changes and physiological stress. The results of an interdisciplinary study conducted on the remains of four individuals show how the various analyses complement and/or corroborate each other, the breadth of their range in understanding how individuals lived and died, and the potential they have for understanding the lives of entire societies in historical periods.
Keywords: aDNA; histologija; histology; interdisciplinarne raziskave; interdisciplinary research; late antiquity; osteologija; osteology; palaeopathology; paleopatologija; pozna antika; stabilni izotopi; stable isotopes